Stock Returns and Output Growth in Emerging and Advanced Economies - Mauro, Paolo (Washington, D.C. : International Monetary Fund, 2000)
This paper studies the correlation between output growth and lagged stock returns in a panel of emerging market economies and advanced economies. It finds that the correlation is as strong in emerging market economies as in advanced economies. Asset prices therefore contain valuable information to forecast output also in emerging market economies. Moreover, the paper finds that the strength of the correlation between output growth and lagged stock returns is significantly related to a number of stock market characteristics, such as the number of listed domestic companies and initial public offerings and, especially, a high market capitalization to GDP ratio and English legal origin.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet